Polyethersulfone Thin-Film Nanocomposite Membrane Embedded with Amine-Functionalized Graphene Oxide for Desalination Applications - Bahaeldin, Ahmed (AUC Knowledge Fountain, 2023)
Thin-film nanocomposite (TFN) desalination membranes were prepared based on a polyethersulfone (PES) support, where the polyamide (PA) layer was embedded with amine-functionalized graphene oxide (GO). The effect of adding various concentrations of functionalized and un-functionalized GO on the desalination performance, hydrophilicity, and morphology of the membranes was additionally assessed throughout this work. Scanning electron microscopy (SEM) measurements were used to assess the morphology of the membranes in combination with Brunauer-Emmett-Teller (BET) analysis. Contact angle measurements were used to gauge the hydrophilicity of the synthesized membranes. The membrane with the best desalination performance contained 1x10-3 wt/vol% of functionalized GO in the PA layer-achieving a 42% improvement in the water flux and a 5.23% compromise in the salt rejection of Na2SO4 compared to a blank thin-film composite (TFC) membrane. The combined use of a PES support with amine-functionalized GO embedded in the PA layer is a novel feature of this work. The first stage entailed the optimization of the PES support layer in order to yield a high pure water permeability (PWP). The support formulation with the highest PWP contained 15 wt% PES and 2.5 wt% polyvinylpyrrolidone (PVP) pore-forming additive. Following this, multiple trials were undergone to produce a PA layer atop the support with the goal of achieving a high salt rejection, before embedding the un-functionalized GO nanomaterials. The PA layer with the highest salt rejection was synthesized using a vacuum filtration technique combined with a sealed mold technique and gave a 97.5% salt rejection of an Na2SO4 solution. Following this step, various concentrations of plain GO were added to the PA layer to find the optimal concentration to incorporate the functionalized GO. Afterwards, the GO was modified with an amine moiety using a carboxyl-activating agent. The success of the functionalization reaction was assessed using FT-IR, Raman, and TEM measurements. Finally, the functionalized GO was added to the PA layer to yield a novel membrane formulation (fTFN).